The cytosolic iron–sulphur cluster assembly mechanism in grapevine is one target of a virulent Crinkler effector from Plasmopara viticola. (7th September 2022) - Xiang, Gaoqing; Fu, Qingqing; Li, Guanggui; Liu, Ruiqi; Liu, Guotian; Yin, Xiao; Chen, Tingting; Xu, Yan
Abstract: Grapevine downy mildew is one of the most devastating diseases in grape production worldwide, but its pathogenesis remains largely unknown. A thorough understanding of the interaction between grapevine and the causal agent, Plasmopara viticola, is helpful to develop alternative disease control measures. Effector proteins that could be secreted to the interaction interface by pathogens are responsible for the susceptibility of host plants. In this study, a Crinkler effector, named PvCRN17, which is from P. viticola and showed virulent effects towards Nicotiana benthamiana previously, was further investigated. Consistently, PvCRN17 showed a virulent effect on grapevine plants. Protein–protein interaction experiments identified grapevine VAE7L1 ( Vitis protein ASYMMETRIC LEAVES 1/2 ENHANCER 7‐Like 1) as one target of PvCRN17. VAE7L1 was found to interact with VvCIA1 and VvAE7, thus it may function in the cytosolic iron–sulphur cluster assembly (CIA) pathway. Transient expression of VAE7L1 in Vitis riparia and N. benthamiana leaves enhanced the host resistance to oomycete pathogens. Downstream of the CIA pathway in grapevine, three iron–sulphur (Fe‐S) proteins showed an enhancing effect on the disease resistance of N. benthamiana . Competitive co‐immunoprecipitation assay showed PvCRN17 could compete with VvCIA1 to bind with VAE7L1 and VvAE7. Moreover, PvCRN17 and VAE7L1 were colocalized at the plasma membrane of the plant cell. To conclude, after intruding into the grapevine cell, PvCRN17 would compete with VCIA1 to bind with VAE7L1 and VAE7, demolishing the CIA Fe‐S cluster transfer complex, interrupting the maturation of Fe‐S proteins, to suppress Fe‐S proteins‐mediated defence responses. Abstract : Two indispensable components of the cytosolic iron–sulphur cluster assembly pathway in grapevine are abducted to the plasma membrane by a virulent CRN effector from Plasmopara viticola to impede grapevine defence responses.